Telaah Diksi Dan Gaya Bahasa Pada Lirik Lagu Sang Dewi Ary Rianto Dan Lyodra Ginting - Lapina Lena; Della Meira; Ilham Arifin; Noerma Kurnia Fajarwati (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The study of diction and style of language in the lyrics of the song Sang Dewi by an Indonesian singer named Lyodra Ginting is the focus of this research. This topic was chosen based on the linguistic elements in the song lyrics. To identify these linguistic elements, this study employs a descriptive qualitative research method based on library sources in the form of research object data, namely the lyrics of the song Sang Dewi, which can be accessed through official digital platforms such as Spotify, and several references in the form of books accessed online and journals whose topic of discussion is similar to this research. Language elements include the style of language and diction used in the lyrics of the song Sang Dewi. The findings of this study are the concluding meanings of the diction and style of language used in the song Sang Dewi.